Manajemen Reputasi Digital PT Pertamina pada Krisis Kepercayaan Publik Akibat Isu Dugaan BBM Oplosan Tahun 2025 - Keisya Amanda Putri; Faiha Alya Nur Isnaini; Zahwa Safira; Azifah Faza Aghnia; Tria Patrianti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study examines PT Pertamina’s digital reputation management in responding to the public trust crisis triggered by allegations of fuel adulteration in 2025. The issue rapidly spread through social media, online news portals, and public discussions, creating negative perceptions of the company’s product quality, transparency, and accountability. Using a descriptive qualitative approach with a case study method, the research analyzes the strategies implemented by PT Pertamina and evaluates their effectiveness in restoring public trust. Data were collected through digital observation, documentation, and a literature review of official company publications, media reports, and public responses across digital platforms. The findings show that PT Pertamina applied several strategies, including clarifying information, issuing a public apology, strengthening its official narrative, establishing a crisis center, testing fuel quality, and involving independent institutions in product verification. These actions reflect the rebuild, diminish, and bolstering dimensions of Situational Crisis Communication Theory. Although the strategies helped reduce issue escalation and develop a counter-narrative, their effectiveness remains limited because negative sentiment and demands for greater transparency persist. Therefore, more open, participatory, consistent, and sustainable digital communication is required to fully restore public trust.